Does Trade Openness Cause Deforestation? A Case Study from Indonesia - Andi Kustanto (Jurnal Ekonomi Pembangunan, 2021)
Forests are unique resources and environments because, in general, they provide many benefits. Changing the function of forest areas to other functions is inseparable from economic development. As a developing country, Indonesia's economy is still dependent on natural resources to support its development. Economic integration through trade openness plays a vital role in economic growth. Policies that enhance the country's ability to trade will help the economy to develop. The more open the trade regime will make the country specialize in semi-finished input products, its competitive advantage. However, economic integration also creates negative externalities in the form of increased deforestation. This study explores the effect of trade openness on deforestation using a panel data method in 20 provinces in Indonesia from 2008-2018. Not many studies have focused on trade openness, large plantations, and social interactions as the driving forces behind deforestation in Indonesia. From the estimation results of the model, it is known that trade openness, economic growth, and activities of logging and forest conversion each contribute to changes in forest cover. If the commodity price rises, it will impact decreasing forest cover. Also, increasing population and density have decreased forest cover because land outside the forest area is limited.